Intrinsic porous polyimide film material and preparation method thereof

By designing polyamide esters with specific side chain structures and forming microporous structures in imidation reactions, the problems of insufficient dielectric and mechanical properties of existing polyimide films are solved, and the preparation of high-performance intrinsic porous polyimide films is realized, which is suitable for microelectronics and new energy fields.

CN119842076AActive Publication Date: 2025-04-18CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510067841.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing polyimide films have shortcomings in terms of dielectric and mechanical properties, which cannot meet the demand for low dielectric constant and high mechanical properties of microelectronic products. At the same time, in terms of lithium-ion battery separators in the new energy field, the heat resistance and electrolyte infiltration performance of existing materials are insufficient.

Method used

The preparation of intrinsic porous polyimide film is achieved by designing polyamide esters with specific side chain structures and forming microporous structures in the imidation reaction. This method does not require external auxiliary processes, and can uniformly form microporous structures, improving the mechanical and dielectric properties of the material.

Benefits of technology

It has achieved the preparation of high-performance intrinsic porous polyimide films, with excellent mechanical properties, heat resistance and dielectric properties, and is suitable for lithium-ion battery separators in microelectronic products and new energy fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244779580000031
    Figure BDA0005244779580000031
  • Figure BDA0005244779580000041
    Figure BDA0005244779580000041
  • Figure BDA0005244779580000051
    Figure BDA0005244779580000051
Patent Text Reader

Abstract

The invention relates to the field of polyimide materials, in particular to an intrinsic porous polyimide film material and a preparation method thereof. According to the preparation method provided by the invention, on the basis of not changing a production mode of producing a polyimide film by a traditional thermal method, a unique polyesteramide intermediate structure of polyesteramide with a special long side chain is designed, and the intrinsic microporous polyimide film is obtained by performing thermal imidization on the polyesteramide with the special long side chain by adopting a commercial film production process mode; only the polymer intermediate is changed, the final structure of the polymer is not changed, post-treatment or surface etching of the film is not needed, the pore-forming groups are uniformly distributed on the main chain of the polymer molecule in the form of chemical bonds, and the uniformity of the pore diameter and the pore is fully ensured. The intrinsic porous polyimide film material prepared by the preparation method provided by the invention has excellent mechanical property, heat resistance and dielectric property and high pore density, and continuous large-scale production of microporous films is more facilitated by adopting a conventional film production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyimide materials, in particular to an intrinsic porous polyimide film material and a preparation method thereof. Background Art

[0002] As a polymer material, polyimide (PI) has been widely used in aerospace, electrical and electronic fields, etc. due to its excellent comprehensive performance advantages such as excellent heat resistance, mechanical properties and chemical stability. PI film is the most widely used and mature product among PI materials. It has promoted the leapfrog development of microelectronic devices, new energy utilization and aerospace technology. However, with the advancement of technology and the iteration of related products, more and more stringent requirements are placed on the performance of polyimide materials.

[0003] The production process of traditional dense polyimide films and the performance differences of different chemical structures have been widely studied, and a relatively mature technical route and structural system have been formed. However, as microelectronic products develop towards miniaturization, lightweight and integration, the wiring spacing in integrated circuits is getting smaller and smaller, and the signal hysteresis caused by capacitive coupling and cross-interference between adjacent wires has increased significantly, and the demand for insulating materials with lower dielectric constants is becoming increasingly urgent. At present, commercial polyimide films can no longer meet the requirements of low dielectric properties. How to reduce the dielectric constant and dielectric loss of PI films is the main problem faced by future updates and iterations of microelectronic products. In other fields, the demand for new polyimide materials is also increasing. For example, in the field of new energy, the diaphragm of lithium-ion secondary batteries is its key component. The widely used polyolefin porous film as the lithium-ion battery diaphragm has the natural disadvantages of low heat resistance and poor wettability with electrolyte. The maximum operating temperature of polyolefin diaphragms is 170°C. The battery will generate heat during the charging and discharging process. Overcharging or improper use will cause rapid accumulation of heat inside the battery. When the temperature exceeds the upper limit temperature of the diaphragm, the diaphragm will shrink and melt, causing the battery to short-circuit and cause combustion and explosion accidents. At present, the safety of lithium-ion batteries has attracted widespread attention from the whole society. Under the national policy of vigorously developing new energy, the development of new diaphragm materials with higher comprehensive performance to replace polyolefin diaphragms has become an urgent problem facing lithium-ion secondary batteries.

[0004] In order to improve the dielectric properties of PI films, previous research and development focused on the design of polymer structures. However, dielectric properties are the essential properties of materials, and it is impossible to significantly reduce the dielectric constant and dielectric loss of materials by changing the structure. It is well known that the dielectric constant of air in nature is 1.0, which is the lowest. If some microporous structures are prepared on PI films to form a polyimide-air two-phase system, the dielectric properties of the material can be greatly improved. By adjusting the structure and proportion of the pore former, the microporous structure can penetrate the pores on both sides of the film.

[0005] At present, there are roughly the following methods for forming pores in polyimide films in existing published patents: electrospinning, physical doping, template method, and phase conversion method.

[0006] 1. Electrospinning: In this method, polymer glue is sprayed into filaments under the action of an electrostatic field, and the sprayed filaments are stacked to form a non-woven film. The pore size of the thin porous structure prepared by this method is relatively large, the mechanical properties of the film are poor, and this method is difficult to achieve large-scale production of porous polyimide films.

[0007] Second, physical doping method, dopants are divided into easily decomposable polymers (polystyrene, polyethylene glycol, etc.), inorganic particles, and inorganic porous fillers. When easily decomposable polymers are used as porogens, when the doping amount is too large, it is very easy to cause pore collapse, and it is difficult to obtain a polyimide film with high porosity. When inorganic substances are used as porogens, after film formation, it is necessary to use strong acid treatment to remove inorganic particles and leave holes on the film. Due to the agglomeration effect, the uniformity of the mixing of inorganic particles is a problem; in addition, it is difficult for the acid to penetrate into the interior of the film, resulting in the porogen residue, and the pores formed are mostly on the outside of the film; at the same time, the acid treatment is very likely to cause degradation of the film structure and have an adverse effect on the mechanical properties of the film.

[0008] 3. Template method: The porous structure obtained by this method has uniform pore size and pore distribution, but this method also has the problem of acid etching after film formation. Therefore, the degradation of the film is inevitable. At the same time, this method is difficult to achieve large-scale production of films.

[0009] Fourth, the phase conversion method, this method is to coat and bake the polyamic acid into a semi-dry film, immerse the semi-dry film in a poor solvent to promote the phase separation of the system, and after the phase separation of the system, the channel for the solvent to precipitate forms voids in the solid phase. The pore structure formed by this method is affected by the residual solvent in the semi-dry film and the precipitation process, and the pore size and pore distribution uniformity formed are poor.

[0010] The above-mentioned various pore-forming methods have achieved the preparation of porous polyimide films, but since each pore-forming method has its own shortcomings, the prepared porous films still have some deficiencies in pore size, pore distribution uniformity, mechanical properties and scalable production, resulting in the inability of porous polyimide films to be widely used in various fields. How to efficiently and low-cost produce porous polyimide films with uniform pore size and pore distribution and excellent comprehensive performance is a difficult problem that needs to be solved urgently. Summary of the invention

[0011] In view of this, the technical problem to be solved by the present invention is to provide an intrinsic porous polyimide film material and a preparation method thereof. The preparation method provided by the present invention can obtain a high-performance intrinsic porous polyimide film material with uniform pore size and porosity.

[0012] The present invention provides an intrinsic porous polyimide film material, which is obtained by imidization reaction of a material including polyamide ester having a structure of formula I;

[0013]

[0014] Wherein, said z≥1000;

[0015] Ar1 and Ar2 are independently selected from substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, substituted or unsubstituted aliphatic groups, substituted or unsubstituted aliphatic heterocyclic groups;

[0016] The M1 and M2 are independently selected from C1 to C 60 An alkyl group or a poly(dimethylsiloxane) group, and the M1 and M2 are the same or different.

[0017] The structural unit of the polyamide ester of the present invention has M1 and M2 side chain groups, wherein M1 and M2 are independently selected from C1 to C 60 alkyl or poly(dimethylsiloxane) group, and the M1 and M2 are the same or different; wherein the C1~C 60 The alkyl groups include C1~C 60 Fatty straight chain alkyl, C1~C 60 The fatty branched alkyl and C1~C 60 The aliphatic cycloalkyl group is preferably C8~C 30 The poly(dimethylsiloxane) group is preferably a poly(dimethylsiloxane) group having a structure of formula Ia;

[0018]

[0019] The x≥1, preferably an integer from 3 to 8;

[0020] The R is a fatty chain.

[0021] In certain embodiments of the present invention, M1 and M2 are independently selected from C8 to C 30 An alkyl group or a poly(dimethylsiloxane) group having a structure of formula Ia, and the M1 and M2 are the same or different.

[0022] The polyamide ester having the structure of formula I of the present invention has a poly(dimethylsiloxane) group, that is, the structural unit of the polyamide ester includes M1 and M2 both selected from C1 to C 60 The structural unit of the alkyl group and at least one of the M1 and M2 is a structural unit selected from the poly(dimethylsiloxane) group. Wherein, the polyamide ester having the structure of formula I has a poly(dimethylsiloxane) group, and the molar amount of the poly(dimethylsiloxane) group accounts for 2% to 50% of the total molar amount of the M1 and M2, preferably 12% to 18%; when the proportion is less than 2%, the resulting material is non-porous or the porosity is too low, and the porosity is ≤8%; when the proportion is higher than 50%, the pore size of the resulting material is too large, the average pore size is ≥20μm, and the mechanical properties of the film drop sharply. The present invention utilizes the M1 and M2 side chain structures in the structural unit of the polyamide ester, and microphase separation and side group breakage and escape occur during the high-temperature cyclization process, thereby forming a microporous structure inside the material. Since the group forming the micropore is grafted on the main chain of the molecule in the form of a chemical bond before imidization, the pore size and pore distribution left when it breaks and escapes are uniform. The intrinsic micropores are formed in a continuous material preparation process without the need for other auxiliary processes, and the macroscopic and microscopic structures of the material are not affected by other factors. Therefore, the intrinsic porous polyimide material has excellent mechanical properties.

[0023] The intrinsic porous polyimide film material of the present invention includes aromatic polyimide materials and copolymerized polyimides thereof as well as block and graft copolymers. Ar1 and Ar2 of the present invention are independently selected from substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, substituted or unsubstituted aliphatic groups, substituted or unsubstituted aliphatic heterocyclic groups. The main chain of the intrinsic porous polyimide film material of the present invention may also contain other heteroatoms, such as polyamideimide, polyhydrazineimide and polyesterimide. Considering the heat resistance of the porous polyimide film, the main chain preferably has an aromatic structure with better high temperature resistance.

[0024] Preferably, the structure of Ar1 has one or more structures of formula Ar1-a to formula Ar1-k;

[0025]

[0026] The structure of Ar2 has one or more structures of formula Ar2-a to formula Ar2-e;

[0027]

[0028] wherein X1 and X2 are independently selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetylamino, ester, acyl, halide or carboxyl;

[0029] The n and m are independently integers of 1 to 4;

[0030] The R 1 and R 3 One independently selected from the groups represented by the structures of Formula 1 to Formula 17;

[0031] The R 2 and R 4 One independently selected from the groups represented by the structures of Formula 1 to Formula 13;

[0032]

[0033] Among them, the X 1 and X 2 independently selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetamido, ester, acyl, halide or carboxyl, preferably selected from -H, -Br, -Cl, -F, -NO2, -CN, -H, -CH3, -CH2CH3, -CH2CH2CH3, isopropyl, isobutyl, tert-butyl, cyclopentyl, cyclohexyl, phenyl or naphthyl;

[0034] The y is an integer of 1-4.

[0035] In the above formulas Ar1-a to Ar1-k, the structure represented by formula Ar1-a is preferably The structure shown in formula Ar1-b is preferably The structure shown in formula Ar1-e is preferably or The structure represented by formula Ar1-h is preferably The structure represented by formula Ar1-i is preferably The R 1 Same as above, no further description is given; the structure shown in formula Ar1-k is preferably The R 2 , X1 and n1 are the same as above and will not be described in detail.

[0036] The intrinsic porous polyimide film material provided by the present invention is an intrinsic porous polyimide film material with intrinsic microporous, high temperature resistance, low dielectric, high strength and high wettability, and has a structure of formula II;

[0037]

[0038] Among them, Ar1, Ar2 and z are the same as described above and will not be repeated herein.

[0039] The present invention also provides a method for preparing the intrinsic porous polyimide film material described in any of the above technical solutions, comprising the following steps:

[0040] The material including polyamide ester is subjected to imidization reaction to obtain an intrinsic porous polyimide film material.

[0041] The polyamide ester of the present invention is the same as that described above and will not be described in detail.

[0042] The reaction formula for obtaining the intrinsic porous polyimide film material by imidization reaction of the polyamide ester of the present invention is as follows:

[0043]

[0044] The present invention adopts the well-known conventional thermal imidization process to carry out an imidization reaction on materials including polyamide ester to obtain an intrinsic porous polyimide film material. The temperature of the imidization reaction of the present invention is 50°C to 350°C, preferably 80°C to 300°C, and the time of the imidization reaction is 0.3h to 30h. The preparation method of the intrinsic porous polyimide film material provided by the present invention only needs to be obtained by thermal imidization of materials including polyamide ester, without precipitation phase separation, acid-base etching and other cumbersome processes that may affect the performance of the film. The formation of pores is controlled by heat treatment in the above-mentioned temperature range, so that the polyamide ester can be gradually imidized to form a polyimide intrinsic microporous film structure.

[0045] Specifically, the present invention sequentially subjects the glue solution including polyamide ester to a pre-baking and curing stage treatment and a post-baking high-temperature treatment to obtain an intrinsic porous polyimide film material; wherein the pre-baking and curing stage treatment is also called a solvent volatilization stage treatment, the temperature of the pre-baking and curing stage treatment is 50°C to 150°C, preferably 80°C to 100°C, and the time of the pre-baking and curing stage treatment is 0.1h to 10.0h. The present invention first subjects the material including polyamide ester to the pre-baking and curing stage treatment to volatilize the solvent of the material to obtain a film material, and the obtained film material is a semi-dry film, which still contains residual solvent, and preferably the mass fraction of the residual solvent accounts for 20% to 50% of the total mass of the semi-dry film.

[0046] The present invention performs the pre-baking and curing stage treatment on the material including polyamide ester, and then performs the post-baking high-temperature treatment on the obtained film material; the post-baking high-temperature treatment includes the imidization stage treatment and the pore-forming material escape stage treatment performed in sequence, the temperature of the imidization stage treatment is 100℃~250℃, preferably 120℃~200℃, and the time of the imidization stage treatment is 0.1h~10.0h; the temperature of the pore-forming material escape stage treatment is 180℃~350℃, preferably 200℃~300℃, and the time of the pore-forming material escape stage treatment is 0.1h~10.0h. The chemical and physical changes in the above three stages are not necessarily carried out completely according to the naming of each stage, and the physical and chemical changes of each stage will overlap. For the sake of clarity, the main physical and chemical changes of the stage are named. In addition to the above-mentioned segmented heating method, the imidization can also be carried out by gradient heating, and the preferred heating rate is 0.1℃ / min~5℃ / min.

[0047] More specifically, the present invention coats the material glue liquid including polyamide ester on a carrier, and sequentially performs a pre-baking and curing stage treatment and a post-baking high-temperature treatment to obtain an intrinsic porous polyimide film material. The present invention coats the material glue liquid including polyamide ester on a carrier using glue liquid coating equipment well known in the art, and the coating method can be slit-type scraping, baffle-type scraping, spin coating, spray coating, and cast coating; the carrier can be a continuous steel strip, polyester film, copper foil, aluminum foil, glass, or mirror steel plate. The present invention performs an imidization reaction on the material including polyamide ester, and in order to facilitate pore formation, a surfactant, a nucleating agent, etc. can be added to perform an imidization reaction together with the material.

[0048] The imidization degree of the intrinsic porous polyimide film material formed by the preparation method of the intrinsic porous polyimide film material provided by the present invention is usually above 90%, and 100% imidization is most preferred. The whole process of imidization reaction can be carried out on a carrier, or after the film is cured after the pre-baking curing stage, the cured film is peeled off the carrier, and the edge of the film is fixed by the needle plate, chain clamp and other equipment used in the existing polyimide film production, and the propped-up film is placed in a high temperature environment to realize the imidization process, which realizes the volatilization of residual solvent and porogen to both sides of the film, avoiding the situation where the solvent evaporates to one side and causes uneven pores on both sides. At the same time, this method matches the existing polyimide film production process and equipment, and achieves the purpose of obtaining a multi-microporous polyimide film using existing equipment, which is conducive to the industrialization of multi-microporous polyimide films.

[0049] Preferably, the method for preparing the intrinsic porous polyimide film material provided by the present invention comprises the following steps:

[0050] S1) reacting a monohydroxy compound with a dianhydride having a structure of formula a; the monohydroxy compound is selected from C1 to C60 An alkyl alcohol and a monohydroxy-terminated poly(dimethylsiloxane) having a structure of formula b;

[0051]

[0052] S2) polymerizing the diamine having the structure of formula c and the reaction product obtained in step S1);

[0053] H2N-Ar2-NH2 formula c;

[0054] S3) performing an imidization reaction on the product obtained in step S2) to obtain an intrinsic porous polyimide film material.

[0055] The reaction formula of the preparation method of the intrinsic porous polyimide film material is as follows:

[0056]

[0057] Specifically, the present invention first reacts a monohydroxy compound with a dianhydride having a structure of formula a under the action of a catalyst, or directly reacts a monohydroxy compound with a dianhydride having a structure of formula a without using a catalyst; wherein the monohydroxy compound is selected from two types, one of which is C1 to C 60 Alkyl alcohols, including C1~C 60 Fatty straight chain alkyl alcohol, C1~C 60 Fatty branched chain alkyl alcohols and C1~C 60 Aliphatic cycloalkyl alcohol, preferably C8~C 30 The other is a monohydroxy-terminated poly(dimethylsiloxane) having a structure of formula b, wherein R and x in formula b are the same as R and x in the aforementioned formula Ia, and are not described in detail; the reaction is an esterification reaction, and a portion of the reaction product is a completely esterified diacid diester, whose structure is The other part is a partially esterified product, and its structural formula is or The M1 and M2 are the same as those mentioned above and will not be described in detail.

[0058] In step S1) of the present invention, the monohydroxyl-terminated poly(dimethylsiloxane) accounts for 2% to 50% of the total amount of the monohydroxyl compound, preferably 12% to 18%. The present invention can effectively control the intrinsic micropore size and pore density of the film by adjusting the proportion of the monohydroxyl-terminated poly(dimethylsiloxane) in the monohydroxyl compound.

[0059] The catalyst in step S1) of the present invention may be added selectively or not, and the catalyst may be a tertiary amine known in the art. The reaction in step S1) of the present invention is carried out in a solvent, and the solvent includes but is not limited to the following compounds: toluene, xylene, dichlorobenzene, ethanol, isopropanol, n-butanol, cyclohexanol, ethylene glycol, ethylene glycol monoethyl ether, ethylene glycol dimethyl ether, 2,2′-dimethoxyethyl ether, acetone, acetonitrile, methyl ethyl ketone, cyclohexanone, tetrahydrofuran, dioxane, N-methylpyrrolidone, N-cyclohexylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, cresol, m-cresol, ethyl acetate, γ-butyrolactone, etc. or a mixture thereof. The temperature of the reaction in step S1) of the present invention is -5°C to 60°C, preferably 0°C to 10°C; the reaction time in step S1) of the present invention is 6h to 16h, and the more specific reaction time varies with the different activities of different reactants.

[0060] In the step S1) of the present invention, after the monohydroxy compound and the dianhydride having the structure of formula a are reacted, the diamine having the structure of formula c and the reaction product obtained in the step S1) are polymerized in the step S2). The reaction materials participating in the polymerization reaction in the step S2) of the present invention include the diamine having the structure of formula c, and the Ar2 is the same as the Ar2 in the aforementioned formula I, and will not be repeated.

[0061] Specifically, step S2) of the present invention includes but is not limited to the following implementation methods:

[0062] Method 1: The reaction product obtained in step S1) is subjected to an acyl chloride reaction, and then the obtained material is subjected to a polymerization reaction with a diamine having a structure of formula c to obtain a viscous polyamide ester-containing adhesive liquid. The acyl chloride reagent of the acyl chloride reaction of the present invention is SOCl2. In this process, the reaction product obtained in step S1) is mainly a completely esterified product diacid diester that is subjected to an acyl chloride reaction to obtain a diester dichloride, and then subjected to a polymerization reaction with a diamine to obtain a viscous polyamide ester-containing adhesive liquid, and the reaction formula is as follows:

[0063]

[0064] Method 2: The reaction product obtained in step S1) is imidazole-treated, and then the obtained material is polymerized with a diamine having a structure of formula c to obtain a viscous polyamide ester adhesive. In this process, the reaction product obtained in step S1) is mainly a completely esterified diacid diester that is imidazole-treated to convert into a diimidazole derivative, and then polymerized with a diamine to obtain a viscous polyamide ester adhesive, and the reaction formula is as follows:

[0065]

[0066] Method 3: The reaction product obtained in step S1) and the diamine having the structure of formula c are polymerized under the action of a condensing agent to obtain a viscous polyamide ester adhesive; the condensing agent includes but is not limited to the following;

[0067]

[0068] The polymerization reaction of the present invention is carried out in a polar solvent, which includes but is not limited to N,N′-dimethylformamide (DMF), N,N′-dimethylacetamide (DMAc), N-methylpyrrolidone, dimethyl sulfoxide (DMSO), tetrahydrofuran / methanol mixture (THF / MeOH), etc.

[0069] In step S2) of the present invention, after the diamine having the structure of formula c and the reaction product obtained in step S1) are subjected to polymerization reaction, the product obtained in step S2) is subjected to imidization reaction to obtain an intrinsic porous polyimide film material. The imidization reaction of the product obtained in step S2) is the same as that described above and will not be repeated.

[0070] The preparation method of the intrinsic porous polyimide film material provided by the present invention, the intrinsic multi-microporous polyimide film finally obtained, the pore size is formed in the process of generating polyimide by thermal imidization of polyamide ester with special structural branches, so the key is to synthesize polyamide ester with special branches and use it as raw material for imidization reaction. In most structures, polyamide acid without branches will also have short-term phase separation through the traditional polyimide film production process, but this phase separation is caused by solvent volatilization and the increase in the degree of molecular chain cyclization to reduce solubility. In traditional film making, the temperature of water and solvent volatilization removed by imidization is far lower than the glass transition temperature (Tg) of the polymer, resulting in the pores left after the water and solvent volatilization are quickly filled with softened polymers, so these polyimide films are dense and non-porous and cannot form a microporous structure. The present invention selects specific structural compounds to be grafted onto the main chain of the molecule to generate polyamide ester with special structural side chains. As the temperature rises, the solvent gradually evaporates. When the temperature rises to a specific temperature, the large fatty side chains and poly(dimethylsiloxane) side chains in the polyamide ester begin to undergo cyclization and side chain shedding, and the polymer gradually transitions from easily soluble polyamide ester to insoluble polyimide. After the large fatty side chains and poly(dimethylsiloxane) side chains fall off, they still remain in the film to promote the occurrence of phase separation in the system. As the temperature rises, the support of the film becomes stronger and stronger, and the detached side chain compounds evaporate and escape from the film, leaving pores inside the film.

[0071] The preparation method of the intrinsic porous polyimide film material provided by the present invention is based on microphase separation, and makes full use of the phase change of the polymer system in the thermal imidization process to obtain an intrinsic microporous polyimide film; it is different from the conventional process of preparing a porous polyimide film based on precipitation phase inversion. The conventional process of producing a porous polyimide film based on precipitation phase inversion is to coat polyamic acid, and then shallowly bake to obtain a polyamic acid semi-dry film, and immerse the polyamic acid semi-dry film in a poor solvent to promote rapid phase separation and precipitation of polyamic acid. In the process of solid-liquid phase separation, liquid (solvent) overflows from the solid phase to form pores. The pores formed in this way have poor uniformity. In the subsequent high-temperature thermal imidization process, the pores will collapse to a certain extent during the dehydration and cyclization of the polymer molecular chain. In the absence of external force (such as supercritical carbon dioxide extraction) support, it is difficult to ensure the formation of pores with uniform pore size and distribution. Since no other steps that may deteriorate the film are involved in the film production process of the present invention, the prepared film retains the intrinsic properties of the polyimide film to the maximum extent. In addition, since the film preparation process fully utilizes the production technology of traditional polyimide films, the prepared porous film has a very high degree of cyclization, and the film has the characteristics of high strength, high toughness and high heat resistance.

[0072] The present invention provides an intrinsic porous polyimide film material and a preparation method thereof. The preparation method of the intrinsic porous polyimide film material provided by the present invention synthesizes a polyamide ester with a special long side chain and subjecting it to thermal imidization to obtain a high-temperature-resistant, high-strength intrinsic microporous polyimide film, which only changes the polymer intermediate without changing the final structure of the polymer, and does not require post-processing or surface etching of the film. The preparation method of the intrinsic porous polyimide film material provided by the present invention is based on the production method of producing polyimide films by the traditional thermal method, by designing a unique polyamide ester intermediate structure, and adopting the most conventional and efficient process in commercial film production to obtain an intrinsic microporous polyimide film, and the pore-forming groups are evenly distributed on the main chain of the polymer molecule in the form of chemical bonds, fully ensuring the uniformity of the pore size and pores. The intrinsic porous polyimide film obtained by the preparation method provided by the present invention has excellent mechanical properties, heat resistance, dielectric properties, high pore density, and the conventional film production process is more conducive to the continuous large-scale production of microporous films. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 1;

[0074] Figure 2 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 2;

[0075] Figure 3This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 3;

[0076] Figure 4 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 4;

[0077] Figure 5 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 5;

[0078] Figure 6 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 6;

[0079] Figure 7 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Comparative Example 1;

[0080] Figure 8 This is the SEM scanning morphology of the micropores of the polyimide film prepared in Comparative Example 2. DETAILED DESCRIPTION

[0081] The present invention discloses an intrinsic porous polyimide film material and a method for preparing the same. A person skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to a person skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0082] The test instruments and conditions for the performance tests of the samples in the comparative examples and embodiments of the present invention are as follows:

[0083] 1. Micromorphology characterization: XL30 (FEI Company, USA) field emission environmental scanning electron microscope (SEM) was used to observe the micromorphology of the microporous polyimide film after gold spraying.

[0084] 2. Heat resistance: TGA-2 thermogravimetric analyzer (TGA), PerkinElmer, USA, heating rate 10°C / min, nitrogen atmosphere.

[0085] 3. Glass transition temperature: static thermomechanical analyzer (TMA Q400), the test atmosphere is nitrogen, the heating rate is 5°C / min, and the temperature range is 40°C to 400°C.

[0086] 4. Mechanical properties: Mechanical properties testing machine (Instron-1121), tensile rate 5mm / min, sample strip size 50mm×10mm, test results are the average of 10 test sample strips;

[0087] 5. Porosity test: The present invention adopts density calculation method. Use a mold knife to cut the porous film into 20mm×20mm square samples, weigh the film mass and measure its thickness, and calculate the density of the sample. The density of polyimide is 1.4g / cm 3 The porosity can be calculated by the following formula.

[0088]

[0089] Where ρ1 is the sample density calculated based on mass and volume, and ρ0 is the polyimide density.

[0090] The molecular weight of the monohydroxy-terminated poly(dimethylsiloxane) used in the specific embodiment of the present invention is in the range of 600 to 6000.

[0091] The present invention will be further described below in conjunction with embodiments:

[0092] Example 1

[0093] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath with the temperature set to 0°C. 10.906g of pyromellitic dianhydride (PMDA) and 120mL of N-methylpyrrolidone were added to the three-necked flask. 10.2g of triethylamine was added and mechanical stirring was started for 30min. 16.398g of lauryl alcohol and 7.252g of poly(dimethylsiloxane) monohydroxy-terminated were slowly added to the reaction solution. After the addition of the materials was completed, the reaction was continued for 8h, the low-temperature cold bath was turned off, and the reaction was continued for 10h at room temperature.

[0094] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min. Then, add 10.012g diaminodiphenyl ether (ODA) in batches and add 100mL N-methylpyrrolidone. Control the temperature of the reaction solution to -5°C. After all ODA is added, turn off the cold bath and continue the reaction at room temperature for 8h. Filter out the solids to obtain a viscous glue solution.

[0095] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1.0 h to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 h; the temperature is further raised to 300°C and kept for 0.5 h to obtain a porous polyimide film.

[0096] The microporous morphology of the prepared polyimide film is shown in Figure 1 As shown, Figure 1This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 1. The relevant performance characteristics of the film are shown in Table 1.

[0097] Example 2

[0098] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath with the temperature set to 0°C. 10.906g of pyromellitic dianhydride (PMDA) and 120mL of N-methylpyrrolidone were added to the three-necked flask. 10.2g of triethylamine was added and mechanical stirring was started for 30min. 11.330g of n-octanol and 7.856g of poly(dimethylsiloxane) with monohydroxyl end-capping were slowly added to the reaction solution. After the addition was completed, the reaction was continued for 8h, the low-temperature cold bath was turned off, and the reaction was continued for 10h at room temperature.

[0099] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min. Then, add 10.012g diaminodiphenyl ether (ODA) in batches and set the reaction liquid temperature to -5°C. After all ODA is added, turn off the cold bath and continue the reaction at room temperature for 8h. Filter out the solids to obtain a viscous glue solution.

[0100] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1.0 h to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 h; the temperature is further raised to 300°C and kept for 0.5 h to obtain a porous polyimide film.

[0101] The microporous morphology of the prepared polyimide film is shown in Figure 2 As shown, Figure 2 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 2. The relevant performance characterization of the film is shown in Table 1.

[0102] Example 3

[0103] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath with the temperature set to 0°C. 14.711g of bis(benzyl)carboxylic acid dianhydride (BPDA) and 120mL of N-methylpyrrolidone were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for 30min. 16.398g of lauryl alcohol and 8.142g of poly(dimethylsiloxane) monohydroxy-terminated were slowly added to the reaction solution. After the addition was completed, the reaction was continued for 8h, the low-temperature cold bath was turned off, and the reaction was continued for 10h at room temperature.

[0104] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 12.13g of thionyl chloride to the reaction bottle and react at low temperature for 6h. After the reaction is completed, add 10.012g of diaminodiphenyl ether (ODA) to the reaction bottle in batches, add 100mL of N-methylpyrrolidone, set the reaction liquid temperature to -5°C, turn off the cold bath after all ODA is added, and continue to react at room temperature for 8h. Filter to obtain a viscous glue solution.

[0105] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film.

[0106] The microporous morphology of the prepared polyimide film is shown in Figure 3 As shown, Figure 3 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 1. The relevant performance characteristics of the film are shown in Table 1.

[0107] Example 4

[0108] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath with the temperature set to 0°C. 14.711g of biphenyltetracarboxylic dianhydride (BPDA) and 120mL of N-methylpyrrolidone were added to the three-necked flask. 7.9g of pyridine was added and mechanical stirring was started for 30min. 11.460g of n-octanol and 8.142g of poly(dimethylsiloxane) with monohydroxyl end-capping were slowly added to the reaction solution. After the addition was completed, the reaction was continued for 8h, the low-temperature cold bath was turned off, and the reaction was continued for 10h at room temperature.

[0109] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 12.13g of thionyl chloride to the reaction bottle and react at low temperature for 6h. Add 10.012g of diaminodiphenyl ether (ODA) in batches and control the temperature of the reaction liquid to around -5°C. After all the ODA is added, turn off the cold bath and continue to react at room temperature for 8h and filter to obtain a viscous glue solution.

[0110] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film.

[0111] The microporous morphology of the prepared polyimide film is shown in Figure 4 As shown, Figure 4 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 1. The relevant performance characteristics of the film are shown in Table 1.

[0112] Example 5

[0113] Place a 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer in a low-temperature cold bath, set the temperature to 0°C, add 14.711g of biphenyltetracarboxylic dianhydride (BPDA) and 120mL of N,N-dimethylacetamide into the three-necked flask, add 10.2g of triethylamine and start mechanical stirring for 30min, slowly add 11.460g of isooctyl alcohol and 7.252g of poly(dimethylsiloxane) monohydroxy-terminated solvent into the reaction solution, continue the reaction for 8h after the addition is completed, turn off the low-temperature cold bath, and continue the reaction at room temperature for 10h.

[0114] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min. Then add 10.012g diaminodiphenyl ether (ODA) in batches and add 100mL N,N-dimethylacetamide to control the temperature of the reaction solution to about -5°C. After all ODA is added, turn off the cold bath and react at room temperature for 8h. Filter out the solids to obtain a viscous glue solution.

[0115] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film is peeled off from the glass plate, and the peeled film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film.

[0116] The microporous morphology of the prepared polyimide film is shown in Figure 5 As shown, Figure 5 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 1. The relevant performance characteristics of the film are shown in Table 1.

[0117] Example 6

[0118] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath with the temperature set to 0°C. 10.906g of pyromellitic dianhydride (PMDA), 120mL of N-methylpyrrolidone and 10.2g of triethylamine were added into the three-necked flask and mechanical stirring was started for 30min. 11.460g of isooctyl alcohol and 8.142g of poly(dimethylsiloxane) with monohydroxyl end-capping were slowly added into the reaction solution. After the addition was completed, the reaction was continued for 8h, and the low-temperature cold bath was turned off. The reaction solution was continued to react for 10h at room temperature.

[0119] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min. Then, add 10.012g diaminodiphenyl ether (ODA) in batches and add 100mL N-methylpyrrolidone. Control the temperature of the reaction solution at around -5°C. After all ODA is added, turn off the cold bath and continue the reaction at room temperature for 8h. Filter out the solids to obtain a viscous glue solution.

[0120] The viscous adhesive liquid synthesized above is degassed statically and then coated on a glass plate, and then placed in an 80°C film drying oven for 0.5 to 2 hours to completely solidify the adhesive film. The adhesive film is peeled off from the glass plate, and the peeled adhesive film is fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature is raised from 120°C to 200°C and kept for 0.5 to 1 hour; the temperature is further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film.

[0121] The microporous morphology of the prepared polyimide film is shown in Figure 6 As shown, Figure 6 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Example 1. The relevant performance characteristics of the film are shown in Table 1.

[0122] Comparative Example 1

[0123] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath and the temperature was set to 0°C. 14.711g of biphenyltetracarboxylic dianhydride (BPDA), 120mL of N,N-dimethylacetamide and 7.9g of pyridine were added into the three-necked flask and mechanical stirring was started for 30min. 18.634g of lauryl alcohol was slowly added into the reaction solution. After the addition was completed, the reaction was continued for 8h and the low-temperature cold bath was turned off. The reaction solution was continued to react for 10h at room temperature.

[0124] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min. Then add 12.415g diaminodiphenyl sulfone (4,4-DDS) in batches and add 100mL N,N-dimethylacetamide. Control the temperature of the reaction solution at around -5°C. After all the ODA is added, turn off the cold bath and continue the reaction at room temperature for 8h. Filter to obtain a viscous glue solution.

[0125] The viscous adhesive solution was degassed and coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film was peeled off from the glass plate, and the peeled film was fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature was raised from 120°C to 200°C and kept for 0.5 hour; the temperature was further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film.

[0126] The microporous morphology of the prepared polyimide film is shown in Figure 7 As shown, Figure 7 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Comparative Example 1. The relevant performance characterization of the film is shown in Table 1.

[0127] Comparative Example 2

[0128] A 500mL three-necked round-bottom flask equipped with a nitrogen inlet and a mechanical stirrer was placed in a low-temperature cold bath with the temperature set to 0°C. 14.711g of biphenyltetracarboxylic dianhydride (BPDA), 120mL of N,N-dimethylacetamide and 7.9g of pyridine were added into the three-necked flask and mechanical stirring was started for 30min. 9.317g of lauryl alcohol and 30.217g of poly(dimethylsiloxane) with monohydroxyl end-capping were slowly added into the reaction solution. After the addition was completed, the reaction was continued for 8h, and the low-temperature cold bath was turned off. The reaction solution was continued to react for 10h at room temperature.

[0129] After the esterification reaction is completed, turn on the low-temperature cold bath and set the temperature to -15°C. After the cold bath temperature reaches the set temperature, add 20.7g DCC to the reaction bottle and continue stirring for about 30min. Then add 12.415g diaminodiphenyl sulfone (4,4-DDS) in batches and add 100mL N,N-dimethylacetamide. Control the temperature of the reaction solution at around -5°C. After all the ODA is added, turn off the cold bath and continue the reaction at room temperature for 8h. Filter to obtain a viscous glue solution.

[0130] The viscous adhesive solution was degassed and coated on a glass plate, and then placed in an 80°C film drying oven for 1 hour to completely solidify the film. The film was peeled off from the glass plate, and the peeled film was fixed on a hollow stainless steel frame and placed in a high-temperature oven. The oven temperature was raised from 120°C to 200°C and kept for 0.5 hour; the temperature was further raised to 300°C and kept for 0.5 hour to obtain a porous polyimide film.

[0131] The microporous morphology of the prepared polyimide film is shown in Figure 8 As shown, Figure 8 This is a SEM scanning morphology of the micropores of the polyimide film prepared in Comparative Example 2. The relevant performance characterization of the film is shown in Table 1.

[0132] Table 1

[0133]

[0134]

[0135] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An intrinsic porous polyimide film material, characterized in that: It is obtained by imidization reaction of a material including polyamide ester having a structure of formula I; Wherein, said z≥1000; Ar1 and Ar2 are independently selected from substituted or unsubstituted aromatic groups, substituted or unsubstituted heteroaromatic groups, substituted or unsubstituted aliphatic groups, substituted or unsubstituted aliphatic heterocyclic groups; The M1 and M2 are independently selected from C1 to C 60 An alkyl group or a poly(dimethylsiloxane) group, and the M1 and M2 are the same or different.

2. The intrinsic porous polyimide film material according to claim 1, characterized in that: The M1 and M2 are independently selected from C8 to C 30 An alkyl group or a poly(dimethylsiloxane) group having a structure of Formula Ia; x≥1; The R is a fatty chain.

3. The intrinsic porous polyimide film according to claim 1, characterized in that: The polyamide ester having the structure of formula I has a poly(dimethylsiloxane) group, and the molar amount of the poly(dimethylsiloxane) group accounts for 2% to 50% of the total molar amount of M1 and M2.

4. The intrinsic porous polyimide film material according to claim 1, characterized in that: The structure of Ar1 has one or more structures of formula Ar1-a to formula Ar1-k; The structure of Ar2 has one or more structures of formula Ar2-a to formula Ar2-e; wherein X1 and X2 are independently selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxyl, alkoxy, phenoxy, cyano, nitro, amino, acetylamino, ester, acyl, halide or carboxyl; The n and m are independently integers of 1 to 4; The R 1 and R 3 One independently selected from the groups represented by the structures of Formula 1 to Formula 17; The R 2 and R 4 One independently selected from the groups represented by the structures of Formula 1 to Formula 13; Among them, the X 1 and X 2 independently selected from hydrogen, alkyl, cycloalkyl, aryl, fluoroalkyl, hydroxy, alkoxy, phenoxy, cyano, nitro, amino, acetamido, ester, acyl, halide or carboxyl; The y is an integer of 1-4.

5. The intrinsic porous polyimide film material according to claim 1, characterized in that: The intrinsic porous polyimide film material has a structure of formula II; 6. The method for preparing the intrinsic porous polyimide film material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The material including polyamide ester is subjected to imidization reaction to obtain an intrinsic porous polyimide film.

7. The method for preparing the intrinsic porous polyimide film material according to claim 6, characterized in that: The specific steps include: S1) reacting a monohydroxy compound with a dianhydride having a structure of formula a; the monohydroxy compound is selected from C1 to C 60 An alkyl alcohol and a monohydroxy-terminated poly(dimethylsiloxane) having a structure of formula b; S2) polymerizing the diamine having the structure of formula c and the reaction product obtained in step S1); H2N-Ar2-NH2 formula c; S3) performing an imidization reaction on the product obtained in step S2) to obtain an intrinsic porous polyimide film material.

8. The method for preparing the intrinsic porous polyimide film material according to claim 7, characterized in that: In step S1), the monohydroxy-terminated poly(dimethylsiloxane) accounts for 2% to 50% of the total amount of the monohydroxy compound.

9. The method for preparing the intrinsic porous polyimide film material according to claim 7, characterized in that: In step S1), the reaction temperature is -5°C to 60°C, and the reaction time is 6h to 16h.

10. The method for preparing the intrinsic porous polyimide film material according to any one of claims 6 to 9, characterized in that: The temperature of the imidization reaction is 50° C. to 350° C., and the time of the imidization reaction is 0.3 h to 30 h.

Citation Information

Patent Citations

  • Diamine and preparation method thereof, and polyimide and preparation method thereof

    CN113387977A

  • Polyimide film with siloxane grafted on side chain

    CN114736409A

  • High-strength poly (siloxane-imide) high-temperature thermoplastic elastomer and preparation method thereof

    CN119192571A

  • Method for manufacturing porous polyimide film and film

    JP2001151929A

  • Polyimide solution for forming porous polyimide film, method for producing porous polyimide film, and porous polyimide film

    JP2017186506A